Effects of various feeding, breeding and management practices on milk production - Dunham, James R. (Kansas Agricultural Experiment Station, 2012)
The March 1984 DHI summary of Kansas Holstein herds shows some interesting correlations of various feeding, breeding, and management factors to production (Table 1). The Rolling Herd Average (RBA) is an excellent evaluation of the efficiency of dairy herds since RHA and income-over-feed-cost are closely related. Although income-over-feed-cost is not profit, it provides the income for paying the other costs of producing milk. The goal of every dairy producer should be to increase the RHA in order to improve profitability.
Keywords: Dairy; Milk production; Feeding; Breeding; Management; Rolling herd average